Sinistralidade e perigosidade rodoviária nos concelhos de Santo Tirso e Trofa - Matos, Fátima do Rosário Magalhães (2013)
The analysis of road accidents within the Municipal Emergency Plans and Civil Protection is critical for the prevention and mitigation of road accidents. This article presents the methodology and results of mapping accidents and dangerous road, using the Geographic Information System (GIS). The case study are the municipalities of Santo Tirso and Trofa, within the Oporto district and the data of road accidents are included in the period 2000 to 2009. The results show the existence of 47 black spots in the municipality of Santo Tirso and 7 black spots of Trofa.